Phenolic acid concentrations in the lumbar cerebrospinal fluid of Parkinsonian patients treated with l-dopa - Pullar, I. A. (1970)
The acid metabolites of dopamine and 5-hydroxytryptamine were estimated in the lumbar cerebrospinal fluid (CSF) of Parkinsonian patients both before and during treatment with l-dopa, the amino acid precursor of dopamine. An attempt was made to relate clinical improvement to the biochemical results. The dopamine metabolites, 3,4-dihydroxyphenylacetic acid and homovanillic acid, showed increases related to the dose of l-dopa, the increase in homovanillic acid concentration being proportionately greater than that of 3,4-dihydroxyphenylacetic acid. The concentration of the 5-hydroxytryptamine metabolite, 5-hydroxyindol-3ylacetic acid, was unaltered by the drug. Clinical improvement, which in the early stages was evident particularly in the bradykinesia, was found to occur at doses of l-dopa greater than 1·5 g/day. Effective doses of l-dopa gave rise to concentrations of dopamine metabolites in the CSF which were greater than normal. Possible implications of these findings are discussed.